A "turn-on" lanthanide complex chemosensor for recognition of lead(ii) based on the formation of nanoparticles. Issue 47 (16th September 2016) - Xu, Benhua; Tang, Xiaoliang; Zhou, Ji'an; Chen, Wanmin; Liu, Haile; Ju, Zhenghua; Liu, Weisheng
Abstract : A pincer ligand could fix effectively Tb 3+ to form complex-based chemosensor, which could further capture Pb 2+ to induce the formation of nanoclusters as a novel recognition mechanism, accompanied with turn-on phosphorescent response of Tb 3+ complex. Abstract : A functional amide-type pincer ligand was designed and synthesized, which could effectively capture Tb 3+ ions to form a phosphorescence complex-based chemosensorTb-1 . The chemosensor could further coordinate with Pb 2+ ions and display a turn-on phosphorescence response. This sensing process was analyzed in detail by steady-state luminescence spectroscopy, time-resolved luminescence spectroscopy, electron microscopy and dynamic light scattering, which suggest that the formation of Pb 2+ -induced hydroxide nanoclusters can adjust the optical signal of the external luminescence compound by embedment and fixation of Tb 3+ complexes. Furthermore, Tb-1 could effectively eliminate the signal interference from the short-lived fluorescence and improve the signal-to-noise ratio to increase the accuracy of the detection for Pb 2+ . An understanding of the recognition mechanism of the Tb 3+ complex-based chemosensor and the application of the characteristic spectra of lanthanide ions might be able to provide more opportunities to develop highly selective optical chemosensors.